Penerapan PSAK No. 405 Akad Mudharabah pada Baitul Maal Wat Tamwil Mandiri Ukhuwah Persada (BMT MUDA) Surabaya - Mifta Royani; Halimatus sa’diyah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2026)
Indonesia, as one of the countries with the largest Muslim populations in the world, has implemented Sharia Accounting Standards (PSAK) to ensure that the recording and presentation of financial transactions in Islamic financial institutions comply with Sharia principles. One of these standards is PSAK 405, which regulates mudharabah accounting and has been effective since January 1, 2024, as part of the renumbering of Sharia Accounting Standards from the 1xx series to the 4xx series. This study aims to examine the implementation of PSAK 405 in mudharabah contracts at BMT Mandiri Ukhuwah Persada (BMT MUDA) Surabaya. This research employs a qualitative approach, with data collected through observation, interviews, and documentation during the period from January 2025 to June 2025. The results indicate that BMT MUDA has fully implemented PSAK 405, covering the aspects of recognition, measurement, presentation, and disclosure. Mudharabah investments are recognized at the time of fund disbursement, measured at the amount of funds provided, and presented in the financial statements at their carrying value. Losses are recognized provided that they are not caused by the negligence of the fund manager. Disclosures include business performance reports, profit-sharing ratios, loss provisions, and mudharabah business activities. However, standard operating procedures in business performance reporting still need to be improved to minimize the potential for fraud.